Does State Aid for Broadband Deployment in Rural Areas Close the Digital and Economic Divide? - Wolfgang Briglauer; Niklas S. Dürr; Oliver Falck; Kai Hüschelrath (Center for Economic Studies and ifo Institute (CESifo), 2018)
We evaluate the impact of a major European state aid programme for broadband deployment applied to rural areas in the German state of Bavaria in the years 2010 and 2011. Using matched difference-in-differences estimation strategies, we find that aided municipalities have – depending on broadband quality – between 18.4 and 25.4 percentage points higher broadband coverage than non-aided municipalities. This increase in broadband coverage, closing the digital divide, results in an average increase of six employed individuals living in the respective aid-receiving municipalities while leaving the number of employed (measured at the place of work) or self-employed individuals and wages unaffected. We therefore conclude that an increase in broadband coverage through state aid protects rural areas from depopulation, but does not contribute to a further closing of the economic divide in the form of creating new jobs.
Keywords: D62; D73; G38; H23; J23; K23; L52; L96; L98; R23; 330; : government policy; state aid; ex-post evaluation; broadband; employment; rural areas; European Union; Germany; Bavaria